Thermoelectric GeTe with Diverse Degrees of Freedom Having Secured Superhigh Performance. Issue 14 (13th February 2019) - Hong, Min; Zou, Jin; Chen, Zhi‐Gang
Abstract: Driven by the ability to harvest waste heat into reusable electricity and the exclusive role of serving as the power generator for deep spacecraft, intensive endeavors are dedicated to enhancing the thermoelectric performance of ecofriendly materials. Herein, the most recent progress in superhigh‐performance GeTe‐based thermoelectric materials is reviewed with a focus on the crystal structures, phase transitions, resonant bondings, multiple valance bands, and phonon dispersions. These features diversify the degrees of freedom to tune the transport properties of electrons and phonons for GeTe. On the basis of the optimized carrier concentration, strategies of alignment of multiple valence bands and density‐of‐state resonant distortion are employed to further enhance the thermoelectric performance of GeTe‐based materials. To decrease the thermal conductivity, methods of strengthening intrinsic phonon–phonon interactions and introducing various lattice imperfections as scattering centers are highlighted. An overview of thermoelectric devices assembled from GeTe‐based thermoelectric materials is then presented. In conclusion, possible future directions for developing GeTe in thermoelectric applications are proposed. The achieved high thermoelectric performance in GeTe‐based thermoelectric materials with rationally established strategies can act as a reference for broader materials to tailor their thermoelectric performance. Abstract : Recent progress in GeTe thermoelectrics is reviewed with a focus on the diverse degrees of freedom to tailor thermoelectric properties. The strategies for enhancing power factors include optimizing carrier concentration, aligning multiple valence bands, density‐of‐state resonant distortion, and increasing band degeneracy by slight symmetry reduction. Decreasing the thermal conductivity can be achieved by intrinsically strengthening the phonon–phonon interactions and introducing planar vacancies.